LABOR PERFORMANCE AND ADMINISTRATIVE MANAGEMENT OF THE PRIVATE UNIVERSITY OF PUCALLPA, 2018-2019 - Panduro Rengifo, Lener Omar (2019)
resulting (P = 0.00 <0.01), which is considered verysignificant, which is why the research hypothesis isaccepted. It is concluded that the labor performancevariable is significantly related with the administrativemanagement of the Private University of Pucallpa2018-2019.